Urinary porphyrin excretion in children with mercury amalgam treatment: findings from the Casa Pia children’s dental amalgam trial - Woods, James S. (2018)
Increases in the urinary concentrations of pentacarboxyl- and coproporphyrins and the appearance of the atypical precoproporphyrin have been defined in relation to mercury (Hg) body burden in animal studies, and this change in the porphyrin excretion pattern has been described as a biomarker of occupational Hg exposure and toxicity in adult human subjects. In the present studies, urinary porphyrins were determined in relation to Hg exposure in children and adolescents, 8–18 yr of age, over the 7-yr course of a clinical trial designed to evaluate the neurobehavioral and renal effects of dental amalgam in children. Subjects were randomized to either dental amalgam or composite resin treatments. Urinary porphyrins and creatinine concentrations were measured at baseline and annually in all subjects. Results were evaluated using linear regression analysis. No significant differences between treatment groups (amalgam versus composite) were found when comparing all subjects for any of the porphyrins of interest. However, incipent amalgam treatment-specific increases were observed in the mean concentrations of penta-, precopro- and coproporphyrins especially when the analyses were restricted to younger subjects (8 to 9 yr old at baseline), and these increases were most apparent during yr 2 through 3 of follow-up, the period of highest mercury exposure from amalgam treatment. Based on the mean number of amalgam fillings received by children in this group (17.8), the renal Hg concentration associated with incipient increases in urinary porphyrins was estimated to be approximately 2.7 μg/g renal cortex. This value corresponds to an observed mean urinary Hg concentration of 3.2 μg/g creatinine, which is approximately fivefold less than that at which renal damage from Hg exposure is estimated to occur in children. These findings are consistent with growing evidence supporting the sensitivity of urinary porphyrins as a biological indicator of subclinical Hg exposure in children.